Austerity, fiscal uncertainty, and economic growth: Insights from fiscally weak EU countries - Giuliano Curatola; Michael Donadelli; Alessandro Gioffré; Patrick Grüning (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Recent empirical evidence suggests that during the last years fiscally weak European countries significantly cut their R&D budgets in an effort to reduce their deficit, according to the spirit of the Fiscal Compact. We propose a general equilibrium model that endogenously captures the trade-off between costs and benefits of austerity measures driven by a zero-deficit policy. Our analysis suggests that cuts in R&D spending undermine economic growth both in the short and the long run. We use our model to estimate the reduction of economic growth due to R&D cuts implemented by fiscally weak European countries during the period 2010-2012. The model predicts a reduction in real growth by 0:63%, 2:93%, and 4:46%, in the next 1, 5, and 10 years, respectively. Moreover, we show that the zero-deficit constraint hampers economic growth in the presence of either a productivity drop or a spending stimulus.
Keywords: E21; E23; E62; G18; 330; Austerity Measures; Fiscal Policy; Endogenous Growth; R&D